Interactive animation media and students' learning interest in learning mathematics in elementary schools - Herawati, Herawati; Septiarini, Virda Putri; Hariyani, Mimi; Hayati, Zikra (Journal of Didactic Mathematics, 2024)
The low interest of students in learning mathematics has an impact on learning outcomes which is one of the efforts in achieving learning goals. One effort that can be made to increase student interest in learning mathematics is to present more interesting materials and guide students to be more active. Thus, teachers are required to be creative and innovative in choosing learning media by adjusting student characteristics and combining media to support student learning interests. This study aims to determine the effect of interactive media on student learning interests. And to determine the completeness of student learning in mathematics material. The type of research used is pre-experimental design with a One-Group-Pretest-Posttest design research design. The sampling technique uses a saturated sampling technique which is all the population in class IV of SD Negeri Rumpet Aceh Besar as many as 24 students, consisting of 11 male students and 13 female students. Data were obtained using a learning interest questionnaire and test questions. Based on the results of the hypothesis test using the Paired Sample t-Test with a significance level of 0.05 (2-tailed), a significance of 0.00 was obtained. This shows that 0.00 < 0.05, then it can be concluded that there is an influence of the use of interactive animation media on the learning interest of students at Rumpet Aceh Besar Elementary School. This is also supported by the percentage of classical completion reaching 100% complete with a KKTP of 75%. Thus, interactive animation media has an effect on students' learning interest with learning outcomes achieving completion.